2014
DOI: 10.1111/andr.285
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum inorganic phosphate with sex steroid hormones and vitamin D in a nationally representative sample of men

Abstract: SUMMARY Defects in bone regulatory pathways have been linked to chronic diseases including cardiovascular disease and cancer. In men, a link between bone metabolism and gonadal hormones has been suggested. However, to date, there is lack of evidence on the association between serum inorganic phosphate (Pi) and sex steroid hormones. The objective of this study was to investigate the association between Pi, sex steroid hormones and a known Pi metabolic regulator, vitamin D, in men in the National Health and Nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 68 publications
3
13
0
Order By: Relevance
“…Some studies have shown a positive association between serum vitamin D levels and total T (Wehr et al, 2010;Lee et al, 2012). Researchers observed a weak link among sex hormones, vitamin D, and Phosphorus in men and reported no associations among men with vitamin D levels above the median (Wulaningsih et al, 2014). In agreement with other studies, we found no correlation between vitamin D and reproductive hormones (Blomberg Jensen et al, 2011;Bjerrum et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…Some studies have shown a positive association between serum vitamin D levels and total T (Wehr et al, 2010;Lee et al, 2012). Researchers observed a weak link among sex hormones, vitamin D, and Phosphorus in men and reported no associations among men with vitamin D levels above the median (Wulaningsih et al, 2014). In agreement with other studies, we found no correlation between vitamin D and reproductive hormones (Blomberg Jensen et al, 2011;Bjerrum et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…An altered sexual hormone status has been shown to lead to nutrition deficiency and various chronic diseases [3334]. According to several studies, vitamin D status influences female reproductive and pregnancy outcomes, and low vitamin D status is associated with impaired fertility, endometriosis, and polycystic ovary syndrome [3536]. Based on various studies, vitamin D levels have an influence on the health of females.…”
Section: Discussionmentioning
confidence: 99%
“…Larger bone indices are associated with sex hormone levels, and bone tissue expresses sex steroid-related enzymes and receptors [29]. Testosterone may influence bone formation together with other calciotropic and phosphotropic hormones; a negative correlation between testosterone and phosphate has been observed in males [30]. Neonates have a minipuberty during the first months of life [31].…”
Section: Discussionmentioning
confidence: 99%